Effect of surface roughness on tyre characteristics. (August 2022) - Becker, Carl; Els, Schalk
Highlights: Measuring terrain surface roughness. Static tyre characterisation tests on different surfaces. Tyre characteristics for different tread wear conditions. Static tyre vs. rolling tyre testing. Abstract: Tyre characterisation is not a trivial or inexpensive exercise thus it is important to obtain representative measurements during tyre characterisation tests. Different test methods exist and vary from laboratory tests to outdoor tests on different surfaces. Each of the test surfaces have different surface roughness and will result in different tyre characteristics. This study compares friction coefficient measurements on dry non-deformable surfaces for laboratory test surfaces and outdoor test tracks on the same agricultural tyre with large lugs at two inflation pressures and three tread wear conditions. The influence of surface roughness on friction coefficient is investigated. The macrotexture and microtexture of multiple surfaces are measured and compared. The importance of measuring the microtexture of the outdoor test surface is noted. Static/Non-rolling tyre tests in a laboratory are compared to Static/Non-rolling tyre tests as well as Dynamic/Rolling tyres tests at an outdoor test facility. Excellent correlation is found between the Static vs. Dynamic and laboratory vs. outdoor tests results when the laboratory tests are conducted on a surface representing the outdoor surface.